Lithium aluminate composite saggar, preparation method and application thereof

By adding synthetic lithium aluminate to the crucible formulation, the problem of alkaline corrosion of the crucible in the production of lithium battery cathode materials was solved, extending the service life of the crucible and improving its durability and thermal shock resistance.

CN120829303BActive Publication Date: 2025-12-12HUNAN DJY-TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511342211.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-12-12
Estimated Expiration
2045-09-19

AI Technical Summary

Technical Problem

In the current production process of lithium battery cathode materials, the crucible is subjected to alkaline corrosion by Li2O during high-temperature calcination, resulting in structural damage and shortened service life.

Method used

Synthetic lithium aluminate was added to the crucible formulation system, and lithium aluminate precursor was prepared by ultrasonic treatment and sintering to form a solid solution, which improved the density and alkali resistance of the material and reduced the coefficient of thermal expansion. Graphene was doped using the sol-gel method to enhance alkali resistance and thermal shock resistance.

Benefits of technology

It effectively slows down the alkaline corrosion of the sagger, extends its service life, and improves the durability and thermal shock resistance of the sagger.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120829303B_ABST
    Figure CN120829303B_ABST
Patent Text Reader

Abstract

The application discloses a lithium aluminate composite saggar and a preparation method and application thereof, and belongs to the technical field of saggar, wherein the saggar comprises an inner surface working layer and an outer matrix layer from inside to outside; the thickness of the inner surface working layer is 1-3 mm; the inner surface working layer comprises the following preparation raw materials in parts by weight: synthetic lithium aluminate 5-20 parts, kaolin 2-10 parts, fused zirconium mullite 0-10 parts, zirconium oxide 0-15 parts, zirconium silicate 0-10 parts, spinel 60-80 parts, alumina 0-10 parts, organic binder 0-5 parts, and water 1-5 parts. The synthetic lithium aluminate is added in the saggar formula system, the structure is solidified during saggar firing, according to the principle of Fick's first law, the addition of lithium aluminate can slow down the alkali corrosion of the material to the saggar, effectively restrict the volume change in the positive electrode material, and effectively improve the service life of the saggar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sagger technology, specifically to a lithium aluminate composite sagger, its preparation method, and its application. Background Technology

[0002] The cathode material for lithium batteries must be sintered in a high-temperature roller kiln at around 1000℃. The raw materials used are mainly nickel-cobalt-manganese / nickel-cobalt-aluminum oxides and lithium carbonate or lithium hydroxide, which provide the lithium source. It is used in a strongly alkaline environment, so the firing process must be carried out in a sagger that can withstand high temperature, resist alkaline oxidation and corrosion, and does not crack.

[0003] The sagger materials used in the production of lithium-ion battery cathode materials are mainly mullite, mullite-cordierite, and corundum-mullite. The lithium-ion battery cathode material production process uses Li₂CO₃ or LiOH·H₂O, which decompose into Li₂O during high-temperature calcination. Because Li₂O has strong alkaline corrosive power, it reacts with Al₂O₃ and SiO₂ to produce LiAlO₂ and LiAlSiO₄. Therefore, the cathode raw materials exert significant alkaline corrosiveness on the sagger, requiring the sagger to have high corrosion resistance.

[0004] Therefore, this application is submitted. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the existing technology and provide a lithium aluminate composite sagger, its preparation method and application. This invention adds synthetic lithium aluminate to the sagger formulation system, which solidifies the structure during sagger firing. According to the principle of Fick's first law, adding lithium aluminate can slow down the alkaline corrosion of the sagger by the material, effectively control the volume change in the positive electrode material, and effectively improve the service life of the sagger.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] A lithium aluminate composite crucible, the crucible comprising an inner working layer and an outer substrate layer from the inside out; the thickness of the inner working layer is 1~3mm;

[0008] The inner surface working layer comprises the following raw materials in parts by weight: 5-20 parts of synthetic lithium aluminate, 2-10 parts of kaolin, 0-10 parts of fused zircon mullite, 0-15 parts of zirconium oxide, 0-10 parts of zirconium silicate, 60-80 parts of spinel, 0-10 parts of alumina, 0-5 parts of organic binder, and 1-5 parts of water.

[0009] The method for preparing the synthetic lithium aluminate is as follows: a lithium source and an aluminum source are mixed evenly to obtain a mixture. The mixture, zirconium nitrate, yttrium nitrate, graphite, and polyvinylpyrrolidone are added to a solvent, stirred evenly, ultrasonically treated, centrifuged, sintered, crushed, and sieved to obtain the synthetic lithium aluminate.

[0010] The inventors of this invention discovered that during the production of cathode materials, lithium oxide reacts with aluminum oxide and silicon oxide in the crucible to generate LiAlO2 and LiAlSiO4. Lithium aluminate accumulates during its formation, and each formation causes a volume change, affecting the crucible's alkali corrosion resistance. In the initial stages of use, the alkali corrosion is relatively slow, so it doesn't cause significant changes. However, with increased usage, once the lithium aluminate on the crucible surface accumulates to a certain amount, a large volume change occurs, leading to peeling and eventual scrapping of the crucible. This invention creatively incorporates synthetic lithium aluminate into the crucible formulation, solidifying its structure during crucible firing. Based on Fick's First Law, adding lithium aluminate slows down the alkali corrosion of the crucible, effectively controlling volume changes in the cathode material and significantly improving the crucible's lifespan.

[0011] This invention involves first uniformly mixing lithium and aluminum sources, then adding the mixture along with zirconium nitrate, yttrium nitrate, graphite, and polyvinylpyrrolidone into a solvent. The mixture is then ultrasonically sintered to obtain synthetic lithium aluminate. Doping is performed using a sol-gel method, where the lithium aluminate precursor, zirconium nitrate, and yttrium nitrate are mixed. Zirconium and yttrium form a solid solution within the lithium aluminate lattice, and their synergistic effect not only increases the material's density and reduces the penetration channels of alkaline substances but also lowers the coefficient of thermal expansion and increases the thermal conductivity, thereby simultaneously improving alkali resistance and thermal shock resistance. Finally, the graphite is exfoliated in situ to generate graphene, effectively enhancing alkali resistance and thermal shock resistance.

[0012] As a preferred embodiment of the present invention, the inner surface working layer comprises the following raw materials in parts by weight: 5-15 parts of synthetic lithium aluminate, 5-7 parts of kaolin, 8-12 parts of zirconium oxide, 70-80 parts of spinel, 5-8 parts of alumina, 1-2 parts of organic binder, and 3-4 parts of water.

[0013] In a preferred embodiment of the present invention, the particle size of the synthesized lithium aluminate is 200-1000 mesh;

[0014] The solvent is N-methylpyrrolidone.

[0015] In a preferred embodiment of the present invention, the molar ratio of lithium in the lithium source to aluminum in the aluminum source is 1:(1~1.1).

[0016] The mass ratio of the mixture, zirconium nitrate, yttrium nitrate, graphite, polyvinylpyrrolidone, and solvent is 1:(0.08~0.15):(0.08~0.15):(0.1~0.2):(4~10).

[0017] In a preferred embodiment of the present invention, the power of the ultrasonic treatment is 400~800W, and the ultrasonic treatment time is 1~2h;

[0018] The sintering temperature is 1300~1400℃, and the sintering time is 1~5h.

[0019] In a preferred embodiment of the present invention, the particle size of the alumina is 2~10μm.

[0020] In a preferred embodiment of the present invention, the particle size of the electrofused zircon mullite is 200-400 mesh.

[0021] In a preferred embodiment of the present invention, the zirconium oxide has a particle size of 100-400 mesh.

[0022] In a preferred embodiment of the present invention, the zirconium silicate has a particle size of 1000-3000 mesh.

[0023] In a preferred embodiment of the present invention, the lithium source is at least one of lithium carbonate and lithium hydroxide.

[0024] In a preferred embodiment of the present invention, the aluminum source is activated alumina.

[0025] As a preferred embodiment of the present invention, the outer substrate layer comprises the following raw materials in parts by weight: 6-12 parts of M70 sintered mullite, 10-25 parts of α-alumina, 1-4 parts of talc, 20-35 parts of fused silica, 25-35 parts of cordierite, 1-5 parts of potassium feldspar, 2-5 parts of dextrin, and 2-6 parts of water.

[0026] As a preferred embodiment of the present invention, the organic binder and each binder independently include at least one of sodium lignosulfonate, calcium lignosulfonate, peach gum, yellow dextrin, white dextrin, polyvinyl alcohol, polyethylene glycol, 801 glue powder, carboxymethyl cellulose, and hydroxypropyl methyl cellulose.

[0027] In a preferred embodiment of the present invention, the spinel comprises a first spinel, a second spinel, and a third spinel in a mass ratio of (5~15):(35~70):(20~30);

[0028] The first spinel has a grain size of 200-400 mesh;

[0029] The second spinel has a grain size of 0.5~1mm;

[0030] The third spinel has a grain size of 1~2mm.

[0031] This invention also provides a method for preparing a lithium aluminate composite crucible, comprising the following steps:

[0032] (1) Weigh each raw material of the inner surface working layer according to the ratio, mix water and organic binder evenly to obtain organic binder solution, premix the remaining materials evenly to obtain premix, mix the premix with organic binder evenly, age, and pass through a 2-3 mesh sieve to obtain inner surface working layer material;

[0033] (2) Weigh each raw material of the outer matrix layer according to the ratio, mix water and binder evenly to obtain binder solution, premix the remaining materials evenly, mix them evenly with binder solution, age, and pass through a 2-3 mesh sieve to obtain outer matrix layer material;

[0034] (3) The inner surface working layer material and the outer substrate material are added into the mold, pressed, dried, and sintered at 1300~1400℃ for 1~10h to obtain lithium aluminate composite sagger.

[0035] This invention also provides an application of lithium aluminate composite crucible in the preparation of cathode materials.

[0036] The beneficial effects of this invention are as follows: By adding synthetic lithium aluminate to the sagger formulation system, the structure is solidified during sagger firing. According to the principle of Fick's first law, the addition of lithium aluminate can slow down the alkaline corrosion of the sagger by the material, effectively prepare the volume change in the positive electrode material, and effectively improve the service life of the sagger. Attached Figure Description

[0037] Figure 1 This is a schematic diagram showing white spots appearing on the sagger. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0039] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0040] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0041] In this application, there are no particular restrictions on the specific dispersion and mixing methods.

[0042] Unless otherwise specified, all components, raw materials, or instruments used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.

[0043] The following embodiments are provided to facilitate understanding of the invention. These embodiments are not intended to limit the scope of the claims.

[0044] Example 1

[0045] A lithium aluminate composite sagger, the sagger comprising an inner working layer and an outer substrate layer from the inside out; the thickness of the inner working layer is 2 mm.

[0046] The inner surface working layer comprises the following raw materials in parts by weight: 10 parts synthetic lithium aluminate, 7 parts kaolin, 8 parts zirconium oxide, 75 parts spinel, 5 parts alumina, 1.5 parts sodium lignosulfonate, and 3.5 parts water.

[0047] The alumina has a particle size of 5 μm.

[0048] The zirconium oxide has a particle size of 200 mesh.

[0049] The zirconium silicate has a particle size of 2000 mesh.

[0050] The kaolin has a particle size of 325 mesh.

[0051] The spinel comprises a first spinel, a second spinel, and a third spinel in a mass ratio of 15:35:25; the first spinel has a particle size of 325 mesh; the second spinel has a particle size of 0.5~1 mm; and the third spinel has a particle size of 1~2 mm.

[0052] The method for preparing the synthetic lithium aluminate is as follows: lithium source (lithium carbonate, particle size 5μm) and aluminum source (active alumina, Al2O3 purity > 99.5%, particle size 2μm) are mixed evenly at a lithium to aluminum molar ratio of 1:1.05 to obtain a mixture. The mixture, zirconium nitrate, yttrium nitrate, graphite, and polyvinylpyrrolidone are added to N-methylpyrrolidone, stirred evenly, ultrasonically treated, centrifuged, sintered at 1350℃ for 4h, crushed, and sieved to obtain synthetic lithium aluminate with a particle size of 325 mesh. The ultrasonic treatment power is 600W and the ultrasonic treatment time is 1.5h. The mass ratio of the mixture, zirconium nitrate, yttrium nitrate, graphite, polyvinylpyrrolidone, and solvent is 1:0.15:0.08:0.2:4.

[0053] The outer substrate layer comprises the following raw materials in parts by weight: 8 parts of M70 sintered mullite 200 mesh, 17.5 parts of α-alumina, 2 parts of talc, 28 parts of fused silica, 30.5 parts of cordierite, 3 parts of potassium feldspar, 3 parts of dextrin, and 4 parts of water.

[0054] The fused silica has a particle size of 1-2 mm, the cordierite has a particle size of 1-2 mm, the M70 sintered mullite has a particle size of 200 mesh, the α-alumina has a particle size of 5 μm, the talc has a particle size of 10 μm, and the potassium feldspar has a particle size of 325 mesh.

[0055] The preparation method of the lithium aluminate composite crucible includes the following steps:

[0056] (1) Weigh each raw material of the inner surface working layer according to the ratio, mix water and organic binder evenly to obtain organic binder solution, premix the remaining materials evenly to obtain premix, mix the premix with organic binder evenly, age, and pass through a 2-mesh sieve to obtain inner surface working layer material.

[0057] (2) Weigh each raw material of the outer matrix layer according to the ratio, mix water and binder evenly to obtain binder solution, premix the remaining materials evenly, mix them evenly with binder solution, age, and pass through a 2-mesh sieve to obtain outer matrix layer material;

[0058] (3) The inner working layer material and the outer substrate material are added into the mold, pressed, dried and sintered to obtain a lithium aluminate composite sagger; the sintering temperature is 1350℃ and the sintering time is 8h.

[0059] Example 2

[0060] The difference between Example 2 and Example 1 is that the formulation of the inner surface working layer is different, but everything else is the same.

[0061] The inner surface working layer comprises the following raw materials in parts by weight: 5 parts synthetic lithium aluminate, 5 parts kaolin, 10 parts zirconium oxide, 70 parts spinel, 6 parts alumina, 2 parts sodium lignosulfonate, and 3 parts water.

[0062] The spinel comprises a first spinel, a second spinel, and a third spinel in a mass ratio of 5:35:30; the first spinel has a particle size of 325 mesh; the second spinel has a particle size of 0.5~1 mm; and the third spinel has a particle size of 1~2 mm.

[0063] Example 3

[0064] The difference between Example 3 and Example 1 is that the formulation of the inner surface working layer is different, but everything else is the same.

[0065] The inner surface working layer comprises the following raw materials in parts by weight: 15 parts synthetic lithium aluminate, 6 parts kaolin, 12 parts zirconium oxide, 80 parts spinel, 8 parts alumina, 1 part sodium lignosulfonate, and 4 parts water.

[0066] The spinel comprises a first spinel, a second spinel, and a third spinel in a mass ratio of 15:45:20; the first spinel has a particle size of 325 mesh; the second spinel has a particle size of 0.5~1 mm; and the third spinel has a particle size of 1~2 mm.

[0067] Example 4

[0068] The difference between Example 4 and Example 1 is that the preparation parameters for synthesizing lithium aluminate are different, but everything else is the same.

[0069] The method for preparing the synthetic lithium aluminate is as follows: lithium source (lithium carbonate, particle size 5μm) and aluminum source (active alumina, Al2O3 purity > 99.5%, particle size 2μm) are mixed evenly at a lithium to aluminum molar ratio of 1:1.05 to obtain a mixture. The mixture, zirconium nitrate, yttrium nitrate, graphite, and polyvinylpyrrolidone are added to N-methylpyrrolidone, stirred evenly, ultrasonically treated, centrifuged, sintered at 1350℃ for 4h, crushed, and sieved to obtain synthetic lithium aluminate with a particle size of 325 mesh. The ultrasonic treatment power is 600W and the ultrasonic treatment time is 1.5h. The mass ratio of the mixture, zirconium nitrate, yttrium nitrate, graphite, polyvinylpyrrolidone, and solvent is 1:0.08:0.15:0.1:10.

[0070] Example 5

[0071] The difference between Example 5 and Example 1 is that the composition of spinel is different, but everything else is the same.

[0072] The inner surface working layer comprises the following raw materials in parts by weight: 10 parts synthetic lithium aluminate, 7 parts kaolin, 8 parts zirconium oxide, 75 parts spinel, 5 parts alumina, 1.5 parts sodium lignosulfonate, and 3.5 parts water.

[0073] The spinel comprises a second spinel and a third spinel in a mass ratio of 35:25; the second spinel has a particle size of 0.5~1mm; and the third spinel has a particle size of 1~2mm.

[0074] Example 6

[0075] The difference between Example 6 and Example 1 is that the composition of spinel is different, but everything else is the same.

[0076] The inner surface working layer comprises the following raw materials in parts by weight: 10 parts synthetic lithium aluminate, 7 parts kaolin, 8 parts zirconium oxide, 75 parts spinel, 5 parts alumina, 1.5 parts sodium lignosulfonate, and 3.5 parts water.

[0077] The spinel comprises a first spinel and a second spinel in a mass ratio of 15:35; the first spinel has a particle size of 325 mesh; and the second spinel has a particle size of 0.5~1 mm.

[0078] Example 7

[0079] The difference between Example 7 and Example 1 is that the composition of spinel is different, but everything else is the same.

[0080] The inner surface working layer comprises the following raw materials in parts by weight: 10 parts synthetic lithium aluminate, 7 parts kaolin, 8 parts zirconium oxide, 75 parts spinel, 5 parts alumina, 1.5 parts sodium lignosulfonate, and 3.5 parts water.

[0081] The spinel comprises a first spinel and a third spinel in a mass ratio of 15:25; the first spinel has a particle size of 325 mesh; and the third spinel has a particle size of 1~2 mm.

[0082] Comparative Example 1

[0083] The difference between Comparative Example 1 and Example 1 is that the inner surface working layer of Comparative Example 1 does not contain synthetic lithium aluminate, but all other aspects are the same.

[0084] The inner surface working layer comprises the following raw materials in parts by weight: 7 parts kaolin, 8 parts zirconium oxide, 75 parts spinel, 5 parts alumina, 1.5 parts sodium lignosulfonate, and 3.5 parts water.

[0085] Comparative Example 2

[0086] The difference between Comparative Example 2 and Example 1 is that the preparation method of lithium aluminate is different, but everything else is the same.

[0087] The preparation method of the synthetic lithium aluminate described in this comparative example is as follows: lithium source (lithium carbonate, particle size 5μm) and aluminum source (active alumina, Al2O3 purity > 99.5%, particle size 2μm) are mixed evenly at a lithium to aluminum molar ratio of 1:1.05 to obtain a mixture. The mixture is sintered at 1350℃ for 4h, crushed, and sieved to obtain synthetic lithium aluminate with a particle size of 325 mesh.

[0088] Comparative Example 3

[0089] The difference between Comparative Example 3 and Example 1 is that the preparation method of lithium aluminate is different, but everything else is the same.

[0090] The method for preparing the synthetic lithium aluminate is as follows: lithium source (lithium carbonate, particle size 5μm) and aluminum source (active alumina, Al2O3 purity > 99.5%, particle size 2μm) are mixed evenly at a lithium to aluminum molar ratio of 1:1.05 to obtain a mixture. The mixture, graphite, and polyvinylpyrrolidone are added to N-methylpyrrolidone, stirred evenly, ultrasonically treated, centrifuged, sintered at 1350℃ for 4h, crushed, and sieved to obtain synthetic lithium aluminate with a particle size of 325 mesh. The ultrasonic treatment power is 600W and the ultrasonic treatment time is 1.5h. The mass ratio of the mixture, graphite, polyvinylpyrrolidone, and solvent is 1:0.2:4.

[0091] Comparative Example 4

[0092] The difference between Comparative Example 4 and Example 1 is that the preparation method of lithium aluminate is different, but everything else is the same.

[0093] The method for preparing the synthetic lithium aluminate is as follows: lithium source (lithium carbonate, particle size 5μm) and aluminum source (active alumina, Al2O3 purity > 99.5%, particle size 2μm) are mixed evenly at a lithium to aluminum molar ratio of 1:1.05 to obtain a mixture. The mixture, zirconium nitrate, yttrium nitrate, and polyvinylpyrrolidone are added to N-methylpyrrolidone, stirred evenly, ultrasonically treated, centrifuged, sintered at 1350℃ for 4h, crushed, and sieved to obtain synthetic lithium aluminate with a particle size of 325 mesh. The ultrasonic treatment power is 600W and the ultrasonic treatment time is 1.5h. The mass ratio of the mixture, zirconium nitrate, yttrium nitrate, polyvinylpyrrolidone, and solvent is 1:0.15:0.08:4.

[0094] Test case

[0095] 1. Alkali resistance test:

[0096] (1) Add the ternary cathode material precursor and Li2CO3 into a ball mill jar in a certain proportion, add grinding balls in a 1:1 mass ratio, and grind for 30 min to obtain a mixture;

[0097] (2) Cut the composite saggers of the examples and comparative examples into sagger pieces, and prepare complete composite saggers;

[0098] (3) Place the mixture from step (1) at the center of the crucible piece, place the crucible piece into the complete composite crucible, heat to 950°C at a heating rate of 5°C / min, hold for 10 hours, then cool to 250°C at a cooling rate of 5°C / min, and then allow to cool naturally to room temperature. If no white spots appear on the surface of the crucible, proceed to the next cycle until white spots appear. Figure 1 The number of times the white dots appear is recorded.

[0099] 2. Thermal stability test:

[0100] (1) Heat the thermal shock test furnace to a test temperature of 1100℃±10℃ and stabilize it for 15 minutes. Fill the test sagger with asbestos and place the test sample on the support arm of the thermal shock test furnace.

[0101] (2) Push the sample into the thermal shock test furnace. Wait for the test furnace to heat up to 1100℃±10℃ again and stabilize for 15 minutes. Then, take the sample out using the pull rod.

[0102] (3) Allow the crucible to cool naturally on the support arm until it is no longer red. Use a clamp to transfer the crucible to the support until it cools to room temperature.

[0103] (4) Repeat the operation until the sagger cracks and record the number of times it cracks.

[0104] Table 1

[0105]

[0106] As can be seen from Table 1, the present invention adds synthetic lithium aluminate to the sagger formulation system, which solidifies the structure during sagger firing. According to the principle of Fick's first law, the addition of lithium aluminate can slow down the alkaline corrosion of the sagger by the material, effectively prepare the volume change in the positive electrode material, and effectively improve the service life of the sagger.

[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A lithium aluminate composite crucible, characterized in that, The sagger includes an inner working layer and an outer substrate layer from the inside out; the thickness of the inner working layer is 1~3mm; The inner surface working layer comprises the following raw materials in parts by weight: 5-20 parts of synthetic lithium aluminate, 2-10 parts of kaolin, 0-10 parts of fused zircon mullite, 8-12 parts of zirconium oxide, 0-10 parts of zirconium silicate, 60-80 parts of spinel, 5-8 parts of alumina, 1-2 parts of organic binder, and 1-5 parts of water. The method for preparing the synthetic lithium aluminate is as follows: a lithium source and an aluminum source are mixed evenly to obtain a mixture. The mixture, zirconium nitrate, yttrium nitrate, graphite, and polyvinylpyrrolidone are added to a solvent, stirred evenly, ultrasonically treated, centrifuged, sintered, crushed, and sieved to obtain the synthetic lithium aluminate.

2. The lithium aluminate composite crucible according to claim 1, characterized in that, The inner surface working layer comprises the following raw materials in parts by weight: 5-15 parts of synthetic lithium aluminate, 5-7 parts of kaolin, 8-12 parts of zirconium oxide, 70-80 parts of spinel, 5-8 parts of alumina, 1-2 parts of organic binder, and 3-4 parts of water.

3. The lithium aluminate composite crucible according to claim 1, characterized in that, The particle size of the synthesized lithium aluminate is 200~1000 mesh; The solvent is N-methylpyrrolidone.

4. The lithium aluminate composite crucible according to claim 1, characterized in that, The molar ratio of lithium in the lithium source to aluminum in the aluminum source is 1:(1~1.1).

5. The lithium aluminate composite crucible according to claim 1, characterized in that, The ultrasonic treatment power is 400~800W, and the ultrasonic treatment time is 1~2h; The sintering temperature is 1300~1400℃, and the sintering time is 1~5h.

6. The lithium aluminate composite crucible according to claim 1, characterized in that, The outer matrix layer comprises the following raw materials in parts by weight: 6-12 parts of M70 sintered mullite, 10-25 parts of α-alumina, 1-4 parts of talc, 20-35 parts of fused silica, 25-35 parts of cordierite, 1-5 parts of potassium feldspar, 2-5 parts of dextrin, and 2-6 parts of water.

7. The lithium aluminate composite crucible according to claim 1, characterized in that, The spinel comprises a first spinel, a second spinel, and a third spinel in a mass ratio of (5~15):(35~70):(20~30); The first spinel has a grain size of 200-400 mesh; The second spinel has a grain size of 0.5~1mm; The third spinel has a grain size of 1~2mm.

8. The method for preparing the lithium aluminate composite crucible according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Weigh each raw material of the inner surface working layer according to the ratio, mix water and organic binder evenly to obtain organic binder solution, premix the remaining materials evenly to obtain premix, mix the premix with organic binder solution evenly, age, and pass through a 2-3 mesh sieve to obtain inner surface working layer material; (2) Weigh each raw material of the outer matrix layer according to the ratio, mix water and binder evenly to obtain binder solution, premix the remaining materials evenly, mix them evenly with binder solution, age, and pass through a 2-3 mesh sieve to obtain outer matrix layer material; (3) The inner surface working layer material and the outer substrate material are added into the mold, pressed, dried, and sintered at 1300~1400℃ for 1~10h to obtain lithium aluminate composite sagger.

9. The application of the lithium aluminate composite crucible according to any one of claims 1 to 7 in the preparation of cathode materials.